Asuhan Keperawatan Jiwa Tn.P Dengan Gangguan Defisit Perawatan Diri : Kebersihan Diri Berpakaian / Berhias Diruang Arjuna RSJD Surakarta - Kurniawan, Lilik; , Sahuri Teguh, S.Kep., Ns (2015)
Background: In patients with psychiatric disorders lack of nursing themselves due to changes in the process of thought resulting in the ability to perform self-care activities decreased. Self-care deficit disorder found in Mental Hospital of Surakarta of data in a look at the medical records regarding 1754 self-care deficit from year to year has increased, so in this case the authors interested in taking a case to the client self-care deficit. PURPOSE: to establish and implement nursing care to clients with self-care deficit disorders in Mental Hospital of Surakarta. METHOD : The method used was the case study approach that the scientific metthod is to collect data, analyze the data and draw conclusions. RESULT: After a given nursing care can be obtained results, the client can establish a trusting relationship, clients can get to know about personal hygiene, the client can perform personal hygiene with the help of nurses, clients can perform personal hygiene independently, the client can maintain personal hygiene independently without the help of a nurse. CONCLUSION: The problem of nursing that exist on the client about self-care deficit, basically can be done well and most of the existing problems can be resolved with the help of nurses and family. Basically the family has a very important role in the healing process of the client.